FBI : Enigma - Book 21 Book 21 - Coulter, Catherine (New York : Gallery Books, 2017)
"When Agent Dillon Savich saves Kara Moody from a seemingly crazy man, he doesnt realize he will soon be facing a scientist who wants to live forever and is using John Doe to help him. But when the scientist, Lister Maddox, loses him, he ups the stakes and targets another to take his experiments to the next level. Its a race against time, literally, as Savich and Sherlock rush to stop him and save both present and future victims of his experiments. In the meantime, Cam Wittier and Jack Cabot must track a violent criminal through the Daniel Boone National Forest"--
"An FBI thriller"--Jacket.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Murder -- Investigation; Fiction; Kidnapping -- Investigation; Fiction; Anonymous persons -- Fiction; Curiosities and wonders -- Fiction; Fiction